Effect of ruboxistaurin on visual loss in patients with diabetic retinopathy - Aiello, Lloyd Paul; Davis, Matthew D; Girach, Aniz; Kles, Keri A; Milton, Roy C; Sheetz, Matthew J; Vignati, Louis; Zhi, Xin Eric (Ophthalmology (Rochester, Minn.), 2006)
To evaluate the effect of ruboxistaurin, an orally administered protein kinase C beta (PKC beta) isozyme-selective inhibitor, on vision loss in patients with diabetes. Thirty-six-month, randomized, double-masked, placebo-controlled, parallel, multicenter trial. Six hundred eighty-five patients randomized at 70 clinical sites. Ophthalmologic examination was performed at screening and at each 3-month visit. Retinopathy status was assessed every 6 months with Early Treatment Diabetic Retinopathy Study (ETDRS) standard 7-field 30 degrees color stereoscopic fundus photography. Levels of diabetic retinopathy and diabetic macular edema were determined by 2 independent graders masked to site and treatment assignment, with additional independent adjudication as required. Eligible patients had a best-corrected visual acuity (VA) score of > or =45 letters, retinopathy level > or = 47A and < or = 53E, and no prior panretinal photocoagulation in at least one eye. Effect of oral ruboxistaurin (32 mg/day) on reduction of sustained moderate visual loss (> or =15-letter decrease in ETDRS VA score maintained > or = 6 months) in patients with moderately severe to very severe nonproliferative diabetic retinopathy. Sustained moderate visual loss occurred in 9.1% of placebo-treated patients versus 5.5% of ruboxistaurin-treated patients (40% risk reduction, P = 0.034). Mean VA was better in the ruboxistaurin-treated patients after 12 months. Baseline-to-end point visual improvement of > or =15 letters was more frequent (4.9% vs. 2.4%) and > or =15-letter worsening was less frequent (6.7% vs. 9.9%) in ruboxistaurin-treated patients relative to placebo (P = 0.005). When clinically significant macular edema was >100 microm from the center of the macula at baseline, ruboxistaurin treatment was associated with less frequent progression of edema to within 100 microm (68% vs. 50%, P = 0.003). Initial laser treatment for macular edema was 26% less frequent in eyes of ruboxistaurin-treated patients (P = 0.008). Oral ruboxistaurin treatment reduced vision loss, need for laser treatment, and macular edema progression, while increasing occurrence of visual improvement in patients with nonproliferative retinopathy.